The effect of prior cycling on leg stiffness during running in high perfomance triathletes - Sayers, M.; Gardner, B. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate the influence cycling has on lower limb stiffness during the run leg in triathletes. Seven well trained triathletes completed a triathlon-run (TR; run preceded by a 40 km cycle) and a control-run (CR; run at the same pace as TR, but without a prior cycle). Vertical, hip, knee and ankle stiffness measured during double leg jumping (2.2 Hz) were compared both before and after the cycle leg and between TR and CR conditions. Maximum hip and knee moments and knee joint stiffness were significantly greater immediately following cycling. However, maximum hip moments and hip joint stiffness were lower in CR than TR. This study provided an insight into how joint stiffness is altered following cycling and may help explain the perceived loss of coordination reported frequently by triathletes at the start of the run leg.